Atypical Hemolytic–Uremic Syndrome: A Clinical Review. (January 2016) - Nayer, Ali; Asif, Arif
Abstract : Atypical hemolytic–uremic syndrome (HUS) is a rare life-threatening disorder characterized by microangiopathic hemolytic anemia, thrombocytopenia, and ischemic injury to organs, especially the kidneys. Microvascular injury and thrombosis are the dominant histologic findings. Complement activation through the alternative pathway plays a critical role in the pathogenesis of atypical HUS. Genetic abnormalities involving complement regulatory proteins and complement components form the molecular basis for complement activation. Endothelial cell dysfunction, probably because of the effects of complement activation, is an intermediate stage in the pathophysiologic cascade. Atypical HUS has a grave prognosis. Although mortality approaches 25% during the acute phase, end-stage renal disease develops in nearly half of patients within a year. Atypical HUS has a high recurrence rate after renal transplantation, and recurrent disease often leads to graft loss. Plasma therapy in the form of plasma exchange or infusion has remained the standard treatment for atypical HUS. However, many patients do not respond to plasma therapy and some require prolonged treatment. Approved by the Food and Drug Administration in the treatment of atypical HUS, eculizumab is a humanized monoclonal antibody that blocks cleavage of complement C5 into biologically active mediators of inflammation and cytolysis. Although case reports have shown the efficacy of eculizumab, randomized clinical trials are lacking. Therapeutic strategies targeting endothelial cells have demonstrated promising results in experimental settings. Therefore, inhibitors of angiotensin-converting enzyme, HMG-CoA reductase, and xanthine oxidase as well as antioxidants, such as ascorbic acid, may have salutary effects in patients with atypical HUS.